Identification and host-plant associations of Australian Sericothripinae (Thysanoptera, Thripidae) - Mound, Laurence A.; Tree, Desley (Zootaxa, 2009)
The Sericothripinae is a largely tropical group of about 140 species that are often strikingly bicoloured and have complex surface sculpture, but for which the biology is poorly known. Although 15 genera have been described in this subfamily, only three of these are currently recognised, with five new generic synonymies indicated here. In Australia, Sericothrips Haliday is introduced, with one European species deployed as a weed biological control agent. Hydatothrips Karny comprises 43 species worldwide, with six species found in Australia, of which two are shared with Southeast Asia, and four are associated with the native vine genus, Parsonsia. Neohydatothrips John comprises 96 species worldwide, with nine species in Australia, of which one is shared with Southeast Asia and two are presumably introduced from the Americas. Illustrated keys are provided to the three genera and 16 species from Australia, including six new species [Hydatothrips aliceae; H. bhattii; H. williamsi; Neohydatothrips barrowi, N. bellissi, N. katherinae]. One new specific synonym is recognised [Hydatothrips haschemi Girault (=H. palawanensis Kudo)], also four new generic synonyms [Neohydatothrips John (=Faureana Bhatti; Onihothrips Bhatti; Sariathrips Bhatti; Papiliothrips Bhatti); Sericothrips Haliday (=Susserico- thrips Han)].